POLARIZATION TOMOGRAPHY OF THE POLYCRYSTALINNE STRUCTURE OF HISTOLOGICAL SECTIONS OF HUMAN ORGANS IN DETERMINATION OF THE OLD DAMAGE - Litvinenko, Olexandra; Paliy, Victor; Vуsotska, Olena; Vishtak, Inna; Kumargazhanova, Saule (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2022)
The results of algorithmic approbation of the technique of polarization tomography digital histological study of the age of damage to the myocardium and lung tissue based on the polarization reconstruction of linear birefringence maps are presented. Relationships between the temporal change in the magnitude of statistical moments of 1-4 orders characterizing the distribution of the magnitude of the degree of crystallization of histological sections of the myocardium and lung tissue and the duration of damage were determined. Established time intervals and accuracy of determining the prescription of damage to the myocardium and lung tissue.